Analis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Pada PT. Astra Otoparts, Tbk Periode Tahun 2021-2023 - Evin Isnaini; Fuliah Tyan Kasmono; M. Thoha Ainun Najib (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2024)
Abstract : This study aims to assess the financial performance of PT Astra Otoparts Tbk from 2021 to 2023 using Liquidity, Solvency, Activity, and Profitability Ratios, based on secondary data from financial reports obtained from the IDX website. This study employs a qualitative descriptive method. The findings indicate that Liquidity Ratios and Solvency Ratios are below industry standards, reflecting an unhealthy financial condition, except for the Debt to Equity Ratio which is healthy. Activity Turnover Ratios in 2023 are also below industry averages, although Days of Receivable, Fixed Asset Turnover, and Working Capital Turnover in 2021-2022 show satisfactory conditions. Profitability Ratios, including Profit Margin on Sales, Net Profit Margin, and Return on Investment, remain below industry averages, indicating poor financial health.